طريقة الترجمة الوظيفية المعجمية المعلقة تصور عام و البحث التاريخي عنها (JOURNAL OF INDONESIAN ISLAM, 2011)
This article deals with Metode Terjemah Gandul (MTG, literally “hanging translation method”) or popularly known as utawi iki iku translation method. It presents two points about the method that has been widely used for translating Arabic-Islamic books to local languages in Indonesian pesantrens. First, it denies the prevailing opinion that MTG is unique only to Javanese pesantrens. The paper shows some similar translation methods in other local languages such as Sundanese, Maduranese, and Malay. Second, the researcher promotes three main agendas concerning the MTG history. Although the method is widely used in Indonesia pesantrens and is regarded one of the most valuable pesantrens intellectual properties, its history has not clearly uncovered yet. The three research agendas include: (1) who was the creator of the MTG; (2) what language was initially used; and (3) when was the MTG created. The research gives the limited answer for each question which could lead to further and deeper researches and studies.